Economic Costs of Mass Violent Conflicts: Final Report for the Small Arms Survey, Geneva, Switzerland - Carlos Bozzoli; Tilman Brück; Thorsten Drautzburg; Simon Sottsas (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
This paper provides a critical analysis of the possible methods, data sources and the existing results of the field of 'the economic costs of mass violent conflict' by identifying strengths and weaknesses of the existing literature. The report evaluates content, methods, and data sources of the existing studies. Regarding the content, the studies offer a broad range of tested cause and impact variables. However, their selection of considered factors is quite sketchy, and a general theoretical underpinning is missing. This warrants above all a better understanding of the channels of indirect effects of the economic consequences of mass violent conflicts. Out of the combination of findings from the different studies we can hypothesize that investment, military expenditure, sectoral shifts, and institutions and policies are key channels. To consider the economic costs, aside from accounting, most studies rely on counterfactual regression analyses. Also with respect to the methodology, an evolutionary progress has not taken place in the literature. The most prominent data sets used are the COW and the UCDP/PRIO for conflicts and the Penn World Tables and the World Development Indicators for socioeconomic data. Based on the critical survey of the literature we propose three models for estimating crosscountry costs of mass violent conflict. These models differ by complexity, ranging from standard regression analysis to computable general equilibrium models. We also discuss other forms of violent conflicts and possibilities to analyze them by using the proposed models.
urn:nbn:de:0084-20070330165
Keywords: C1; E2; O11; Q34; 330; Development economics; violence; conflict; war; macro-economics; econometrics; GDP; growth; reconstruction I; Politischer Konflikt; Bürgerkrieg; Krieg; Soziale Kosten; Wirkungsanalyse; Wissenschaftliche Methode; Statistik; Welt